Multi-Story Building Model for Efficient IoT Network Design - Sergey Bushelenkov; Alexander Paramonov; Ammar Muthanna; Ahmed A. Abd El-Latif; Andrey Koucheryavy; Osama Alfarraj; Paweł Pławiak; Abdelhamied A. Ateya (Mathematics, 2023)
This article presents a new network model for IoT that is based on a multi-story building structure. The model locates network nodes in a regular, cubic lattice-like structure, resulting in an equation for the signal-to-noise ratio (SNR). The study also determines the relationship between traffic density, network density, and SNR. In addition, the article explores the potential of percolation theory in characterizing network functionality. The findings offer a new approach to network design and planning, allowing for selecting a network topology that meets criteria and requirements while ensuring connectivity and improving efficiency. The developed analytical apparatus provides valuable insights into the properties of the network and its applicability to specific conditions.